Association between preconception paternal smoking and birth defects in offspring: evidence from the database of the National Free Preconception Health Examination Project in China. (17th May 2020) - Zhou, Q; Zhang, S; Wang, Q; Shen, H; Zhang, Y; Tian, W; Li, X
Abstract : Objective: To clarify whether preconception paternal smoking has any adverse effects on the offspring. Design: Prospective, population‐based study. Setting: Preconception registry data from the National Free Preconception Health Examination Project. Population or sample: Couples planning pregnancy, with complete information on preconception paternal smoking behaviour and pregnancy outcomes. Methods: The effect of questionnaire‐based paternal smoking behaviour during preconception and pregnancy was assessed via logistic regression. Additionally, we performed a 1:1 case–control (birth defects versus normal pregnancy) analysis, matched for maternal province, folic acid supplementation and paternal alcohol consumption. Main outcome measures: Risk of birth defects in offspring. Results: In total, 566 439 couples with complete information on preconception paternal smoking behaviour and pregnancy outcomes were enrolled. The preconception paternal smoking rate was 28.7% (162 482) overall: 8.7% (49 303) stopped smoking, 13.3% (75 517) decreased their smoking, and 6.6% (37 662) continued smoking during early pregnancy. The risk of birth defects was higher in the continued‐smoking ( P < .000, odds ratio [OR] 1.87, 95% CI 1.36–2.56) and decreased‐smoking groups ( P = .007, OR 1.41, 95% CI 1.10–1.82). In the case–control analysis, infants whose fathers stopped ( P = .003, OR 0.32, 95% CI 0.15–0.67) or decreased smoking ( P = .000, OR 0.25, 95% CI 0.13–0.49) were at lower risk of congenital heart diseases, limb abnormalities, digestive tract anomalies and neural tube defects than those whose fathers continued smoking. Conclusion: Preconception paternal smoking may be associated with congenital heart diseases, limb abnormalities and neural tube defects in the offspring. Changes in smoking behaviour may reduce this risk. Tweetable abstract: This study suggests that preconception paternal smoking is associated with birth defects in offspring. Changes in smoking behaviour may reduce this risk. Tweetable abstract: This study suggests that preconception paternal smoking is associated with birth defects in offspring. Changes in smoking behaviour may reduce this risk.